2013
DOI: 10.1002/chem.201203730
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Synthesis of ZnO Nanostructures

Abstract: In this study, we report a simple solution-phase method to prepare ZnO nanostructures with controllable morphologies. By using oleylamine (OAm) and dodecanol (DDL) as solvents, zinc oxide nanocrystals with tunable sizes and diverse shapes (hexagonal pyramids, bulletlike, and pencil-like shapes) have been obtained under mild conditions. At the same time, the introduction of presynthesized gold nanocrystals can also lead to the hybrid nanostructures of gold-zinc oxide hexagonal nanopyramids. In addition, the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 118 publications
2
20
0
Order By: Relevance
“…[001] preferential orientation, as often reported for wurtzite ZnO nanosystems. 17, [24][25]40,47,62 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[001] preferential orientation, as often reported for wurtzite ZnO nanosystems. 17, [24][25]40,47,62 .…”
Section: Resultsmentioning
confidence: 99%
“…ZnO, a biosafe II-VI semiconductor with a wide band gap (E G = 3.4 eV), [1][2][3][4][5][6][7][8] low cost and remarkable stability, [9][10][11][12][13] has been the subject of an ever increasing interest since the 1930s, with a research peak at the end of the seventies. 14 This flourishing attention has been stimulated by the unique zinc oxide properties, [15][16][17][18][19][20] including the large exciton binding energy (60 meV) [1][2][21][22][23] and the spontaneous piezoelectric polarization, [24][25][26][27][28][29] due to the stacking of alternating O 2− and Zn 2+ planes along the c axis of the hexagonal wurtzite structure. 11,[30][31][32][33][34][35] The tailoring of zinc oxide chemical, physical and functional properties as a function of the size and shape of ZnO building blocks offers a huge possibility for a variety of technological enduses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different kinds of ZnO nanomaterials have been developed which presented versatile wettability to water and showed promise for the design of inorganic bio‐inspired nanostructures with special surface properties . Figure (g‐h) shows fly‐eye inspired ZnO microspheres that show a similar structure to the fly compound eyes: the surfaces of the ZnO microspheres consist of hexagonal crystal arrays or nanocones around 200–350 nm in size; and in the middle, there are radial pile‐pore structures that are formed under the nanocones and work as light guide channels in the same way as the rhabdom in natural eyes, while the centre is a round hole that can allow the incorporation of secondary optical elements inside.…”
mentioning
confidence: 99%
“…In the absence of these heterogeneous crystal seeds, hexagonal ZnO pyramids normally form at temperatures of between 160 -180 °C. 31 In the presence of 4 nm seed crystals, we observed that attached, seeded, ZnO nanocrystals were nucleated at reaction temperatures well below 175 °C (see Figure S1). Examination of the TEM images of products produced at lower temperatures of 130 °C, 140 °C and 150 °C revealed that Au-ZnO hexagonal nanocrystal hybrids can form at these temperatures, but it was noted that the ZnO-component morphologies were progressively less complete the lower the temperature was maintained.…”
Section: Temperature-and Time-dependent Studies Of Au-zno Hexagonal Nmentioning
confidence: 95%